Cost and economic burden of adverse events associated with metastatic melanoma treatments in five countries. (1st September 2016) - Vouk, Katja; Benter, Ursula; Amonkar, Mayur M.; Marocco, Alessia; Stapelkamp, Ceilidh; Pfersch, Sylvie; Benjamin, Laure
Abstract: Objective: To estimate per-event cost and economic burden associated with managing the most common and/or severe metastatic melanoma (MM) treatment-related adverse events (AEs) in Australia, France, Germany, Italy, and the UK. Methods: AEs associated with chemotherapy (dacarbazine, paclitaxel, fotemustine), immunotherapy (ipilimumab), and targeted therapy (vemurafenib) were identified by literature review. Medical resource use data associated with managing AEs were collected through two blinded Delphi panel cycles in each of the five countries. Published costs were used to estimate per-event costs and combined with AEs incidence, treatment usage, and MM prevalence to estimate the economic burden for each country. Results: The costliest AEs were grade 3/4 events due to immunotherapy (Australia/France: colitis; UK: diarrhea) and chemotherapy (Germany/Italy: neutropenia/leukopenia). Treatment of AEs specific to chemotherapy (Australia/Germany/Italy/France: neutropenia/leukopenia) and targeted therapy (UK: squamous cell carcinoma) contributed heavily to country-specific economic burden. Limitations: Economic burden was estimated assuming that each patient experienced an AE only once. In addition, the context of settings was heterogeneous and the number of Delphi panel experts was limited. Conclusions: Management costs for MM treatment-associated AEs can be substantial. Results could be incorporated in economic models that support reimbursement dossiers. With the availability of newer treatments, establishment of a baseline measure of the economic burden of AEs will be crucial for assessing their impact on patients and regional healthcare systems.